2012
DOI: 10.1007/s10549-012-2035-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profiling identifies numerous rare drug targets and distinct mutation patterns in different clinical subtypes of breast cancers

Abstract: The mutation pattern of breast cancer molecular subtypes is incompletely understood. The purpose of this study was to identify mutations in genes that may be targeted with currently available investigational drugs in the three major breast cancer subtypes (ER+/HER2−, HER2+, and Triple Negative). We extracted DNA from fine needle aspirations of 267 stage I–III breast cancers. These tumor specimens typically consisted of >80 % neoplastic cells. We examined 28 genes for 163 known cancer-related nucleic acid varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 19 publications
4
66
1
Order By: Relevance
“…Studies that included small numbers of MC demonstrated that mutated PIK3CA, which is found in 16-33% of IDCs, is not a common finding in MC (0-13%), supplementary material, Figure S8 [125,[152][153][154][155][156][157]. Mutations of BRAF and KRAS are not common in breast cancer (0-3% and 2-5%) and associations with MC have not been studied [65,158,159]. Unlike in colorectal MC, MSI is a rare phenomenon in MC of the breast, occurring only sporadically (0-3%) [160][161][162][163][164][165].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
“…Studies that included small numbers of MC demonstrated that mutated PIK3CA, which is found in 16-33% of IDCs, is not a common finding in MC (0-13%), supplementary material, Figure S8 [125,[152][153][154][155][156][157]. Mutations of BRAF and KRAS are not common in breast cancer (0-3% and 2-5%) and associations with MC have not been studied [65,158,159]. Unlike in colorectal MC, MSI is a rare phenomenon in MC of the breast, occurring only sporadically (0-3%) [160][161][162][163][164][165].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
“…Patients with TNBC show a significant worse prognosis compared with other breast cancer subtypes (1). However, increasing evidence indicates that TNBC is a heterogeneous disease that encompasses several distinct entities with remarkably different molecular characteristics and clinical behavior (1)(2)(3). No specific and well-defined molecular targets have so far been found in TNBC and there seem to be few therapeutic options on the horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Lessons learned from FBXW7-associated murine cancer models also convincingly demonstrated that it is a bona fide tumor suppressor gene with extensive functions [26]. Recent genetic profiles of human cancers based on high-throughput sequencing revealed that FBXW7 is among the most frequently mutated cancer genes [28][29][30][31][32][33]. Thus, FBXW7 has been illuminated to be a central mediator in tumorigenesis [34].…”
Section: Discussionmentioning
confidence: 97%